A retrospective analysis of surgical resection of large ear keloids. (1st July 2018) - Lyu, Anqi; Xu, Erwei; Wang, Qiying
Abstract: Objective: To investigate surgical methods for the removal of larger ear keloids. Methods: Two different surgical techniques were used: Method A, tumour excision followed by in situ scar flap repair; and Method B, wedge resection of an auricular lesion followed by primary closure or local flap repair. After the treatment, patients received postoperative, local radiotherapy. Follow‐up was for 1–3 years (median 28.9 months). Results: Twenty patients with 35 large ear keloids were reviewed. In Method A, six ears were cured, three ears improved, five ears relapsed after 1 year and one ear recurred within 1 year. In Method B, 17 ears were cured, two ears improved and one ear recurred within 1 year. Conclusion: Keloid scars can be effectively treated with a combination of radiotherapy and surgical excision.